Effect of Sensory Integration Therapy on Attention Span and Gross Motor Skills in Children with Down Syndrome: A Quasi-experimental Study - Manshi Baberwal; Dimple Choudhry; Anjali; Anshu Kumari; Mallika Jhandai; Pankaj Bhardwaj; Ekta (Journal of Clinical and Diagnostic Research)
Introduction: Down Syndrome (DS) is the most widely recognised intrinsic chromosomal problem that is related with mental retardation. Attention and motor abilities are negatively impacted by intellectual disability. One approach to dealing with the intellectual disability is Sensory Integration Therapy (SIT). Aim: To find out the effect of SIT on attention span and gross motor skills in children with DS. Materials and Methods: The present quasi-experimental study was conducted in various special schools in Rohtak, Haryana, India and at College of Physiotherapy, Pt. BD Sharma PGIMS, Rohtak, Haryana, India, between November 2022 and August 2023. A total of 40 patients were equally divided into two groups: an experimental group (n=20), comprising children with DS and control group (n=20), comprising normal children. Only DS children were provided with 10 sessions (over 5 week) of SIT. Evaluations were done at pretreatment, post-treatment and one month after the post-treatment evaluation in experimental group, while only pretreatment evaluations were conducted in control group. Attention span was measured using Stroop colour and Word Test and gross motor skills were measures with the help of {Gross Motor Function Measure 88 (GMFM-88)}. The data was analysed with the help of independent t-test (for between-group analysis) and repeated measures Analysis of Variance (ANOVA) (for within-group analysis). Results: The mean age of the experimental and control group was 10.30±1.976 years and 10.40±1.273 years, respectively. Both groups had 13 males and seven females. The independent t-test showed a significant difference (p<0.001 and p<0.001) between the attention span and gross motor skills) between the experimental group (71.90±5.22) and control group (118.25±0.786). Repeated measures ANOVA also indicated significant difference (p<0.001 and p<0.001) of attention span between the pretreatment, post-treatment and follow-up values of experimental group (71.90±5.22, 77.40±4.871, 74.45±4.839). Conclusion: The SIT helps in improving the attention span and gross motor skills of children with DS.